Embedded Electronics Applied in Remote Laboratories Using NodeJs - Amine Moulay Taj; Abouhilal, Abdelmoula; Naima Taifi; Abdessamad Malaoui (Iraqi Journal of Science, 2021)
A description of the implementation of integrated practical work in a remote laboratory was presented in this paper. The student, in real time, can access an online web page in order to manipulate a practical work of digital electronics. This work is based on the use of an embedded system PcDuino. The hardware architecture and software solutions are described, as well as the supervision tool that allows the student to follow changes in the output states of the Practical Work remotely.